HADIS TENTANG KEWAJIBAN MENUNTUT ILMU: Stigmatisasi Masyarakat terhadap Perempuan Berpendidikan Tinggi - Siti Afiroh; Nasrulloh Nasrulloh (DIRAYAH : Jurnal Ilmu Hadis, 2025)
The study aims to interpret the meaning of the hadith obligation to seek knowledge and analyze forms of stigma experienced by educated women. This study discusses the hadith on the obligation to seek knowledge in relation to the phenomenon of stigmatization against highly educated women. The issue arises from the gap between Islamic teachings, which emphasize equality in the pursuit of knowledge, and the gender-biased reality still found in society. Using a qualitative-descriptive approach and library research, this study applies Norman Fairclough’s Critical Discourse Analysis (CDA), which includes text, discourse practice, and sociocultural practice analysis. The findings show that the hadith affirms the equal rights and obligations of men and women to seek knowledge. The stigmatization of educated women does not originate from Islamic teachings but from deeply rooted patriarchal social constructs. Therefore, Islamic education must play an active role in eliminating gender bias through inclusive and just religious interpretation. In conclusion, seeking knowledge is a fundamental right of every Muslim regardless of gender, and Islamic education should serve as a means of social transformation toward an egalitarian and civilized society.